2019
DOI: 10.1111/vcp.12703
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic and serum biochemical reference intervals for wild eastern quolls (Dasyurus viverrinus): Variation by age, sex, and season

Abstract: Background: The eastern quoll (Dasyurus viverrinus) is an endangered carnivorous marsupial that has recently suffered significant population declines. Several small captive breeding populations have been established, with plans to translocate wild and captive individuals to areas of their former distribution. Accordingly, hematologic and serum biochemical reference intervals (RIs) established from wild eastern quoll populations are essential for monitoring the health and disease status of both captive and wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…he immune system undergoes ontogenesis (Sidman et al 1987), with many haematological and some serum protein parameters increasing with age (Fancourt and Nicol 2019). Consistent with this, maturity was partitioned in our RI because it was determined as moderately important in our RF model, with adults having signiicantly higher MCV, MCH, MCHC, TP and globulin concentrations than subadults.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…he immune system undergoes ontogenesis (Sidman et al 1987), with many haematological and some serum protein parameters increasing with age (Fancourt and Nicol 2019). Consistent with this, maturity was partitioned in our RI because it was determined as moderately important in our RF model, with adults having signiicantly higher MCV, MCH, MCHC, TP and globulin concentrations than subadults.…”
Section: Discussionsupporting
confidence: 55%
“…18 models, one for each parameter, were created using the 'randomForest' R package. Each factor (site, season, sex, sexual maturity, laboratory, rainfall and temperature) was selected to train the model based on their known influence on haematological and serum protein parameters (Pacioni et al 2013, Fancourt andNicol 2019). Average monthly rainfall and temperature data were obtained from the nearest weather station (Bureau of Meteorology 2020) for the month preceding collection for each site.…”
Section: Influence Of Biotic and Abiotic Factors On Reference Intervamentioning
confidence: 99%
“…Prior to analysis, a log transformation was carried out and normality and collinearity assessed using the Shapiro–Wilk normality test and variance inflation factor (< 2), respectively. The initial factors for all models were selected from relevance in the literature ( Turner et al 2012 ; Fancourt and Nicol 2019 ) and previous work ( Brandimarti et al 2020 ). Factors for N:L ratio model selection are presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Sex is generally associated with variation in serum biochemistry in different species of animals, including fish (Fancourt & Nicol, 2019; Kulkarni, 2017). Studies have reported higher values of these constituents for male individuals compared with females due to the greater depletion of metabolic components by the processes of ovarian development and spawning (Tavares‐Dias et al, 2004) or to behavioural differences between males and females (Kulkarni, 2017).…”
Section: Discussionmentioning
confidence: 99%